Increasing the Creativity and Independence of SD Negeri 47 Palembang Students through Learning to Make Videos about Entrepreneurship - Saputri, Helen (PPSDP International Journal of Education, 2024)
This study aims to increase student creativity and independence at SD Negeri 47 Palembang through learning to make videos about entrepreneurship. The Classroom Action Research (CAR) method was used in this research, which consists of four cycles: planning, implementation, observation, and reflection. The research subjects were class VI A students at SD Negeri 47 Palembang. Data were collected through observation, interviews and questionnaires, then analysed qualitatively and quantitatively. The research results show that learning to make videos about entrepreneurship significantly increases students’ creativity and independence. Students are more active in expressing ideas and completing assignments independently. Implementation of this method has proven effective in developing 21st century skills in students. This research suggests that project-based learning such as making videos about entrepreneurship be integrated into the elementary school curriculum to improve students’ learning skills and motivation.